AB0222 Monocyte-derived IL-32 expression correlates with the level of inflammation in salivary glands of sjÖgren's syndrome. (23rd January 2014) - Murray-Brown, W.; Picarelli, G.; Vartoukian, S.; Sutcliffe, N.; Fortune, F.; Valesini, G.; Pitzalis, C.; Tappuni, A.; Priori, R.; Bombardieri, M.
Abstract : Background: IL-32, a recently described cytokine promoting pro-inflammatory cytokines such as IL-1β, IL-6, CXCL8 and TNFα, has emerged as a key component in the development of chronic inflammatory diseases such as rheumatoid arthritis. Objectives: To we investigate IL-32 expression at transctipt and protein level and identify IL-32 producing cells in the salivary glands (SG) of Sjögren's Syndrome (SS) patients. Methods: IL-32 mRNA expression level was assessed by Taqman quantitative PCR in SG of SS patients and non-specific chronic sialadenitis (NSCS) as controls. Patients and control were enrolled in two different Centres. In addition, immunohistochemistry was used to assess IL-32 expression and the formation of B/T cell aggregates. Double immunofluorescence for IL-32 and CD68 was used to identify the cellular source of IL-32 in the SG. Results: Expression of IL-32 correlated with the severity of inflammation and was significantly increased in SS patients compared to NSCS controls (mean±SEM; 10.3±2.1 vs 4.1±0.5, p<0.005). In addition, IL-32 mRNA correlated with the levels of CXCL13 (Spearman's r=0.50, p=0.004), a lymphoid chemokine strictly associated with the formation of B/T cell aggregates. Immunohistochemistry identified IL-32+ cells in periductal aggregates in SS but not in controls. Conversely, both SS and control SG showed abundant IL-32 staining on salivary ductal epithelial cells. Finally, double immunofluorescence identified monocyte-derived CD68+ cells as the main source of IL-32 within lymphoid aggregates in SS. Conclusions: Here we show that IL-32 expression is significantly increased in the SG of SS patients where both ductal epithelial cells and monocyte-derived cells abundantly express this cytokine. These data strongly implicate IL-32 in the maintenance of chronic inflammation in the target organ of SS. Disclosure of Interest: None Declared